The Impact of eWOM, Brand Image, and Brand Trust on Millennial Fashion Purchase Decisions on Shopee - Maulana, Aldi; Ali, Mochammad Mukti (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Millennials shop for stylish items on Shopee, and this study analyzes how eWOM, brand image, and brand trust influence their purchasing choices. A total of 75 people participated in a survey-based quantitative analysis. SEM was utilized to analyze the data, along with SmartPLS. Based on the data, it is clear that a positive brand image and brand trust significantly influence purchasing choices, while negative eWOM has the opposite effect. The study shows that the level of consumer trust in the brand is the most important factor when making a purchase. With an R-squared value of 0.685, we can see that these three factors explain 68.5% of the variation in consumer purchases. This finding emphasizes the importance of actively managing eWOM, strengthening brand image through digital branding strategies, and increasing trust through service and transparency. This study concludes that digital marketing strategies that focus on brand reputation and customer satisfaction will have a positive impact on purchasing decisions and loyalty of millennial consumers in e-commerce.